2019
DOI: 10.3390/ijerph16111970
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Policy Modifiable Factors on Inequalities in Rates of Child Dental Caries in Australia

Abstract: Background: Poor oral health in childhood can lead to adverse impacts later in life. We aimed to estimate the prevalence and population distribution of childhood dental caries in Australia and investigate factors that might ameliorate inequalities. Methods: Data from the nationally representative birth cohort Longitudinal Study of Australian Children (N = 5107), using questions assessing: The experience of dental caries during each biennial follow-up period (2–3 years to 10–11 years), socioeconomic position (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 44 publications
1
18
0
2
Order By: Relevance
“…Goldfeld et al showed that caries were higher in children with lower socioeconomic status. (14) Factors such as the socioeconomic status represent a few key indicators of the disease, such as the socioeconomic status, and risk factors such as microflora determines that the person is at a low, moderate and high risk of caries, although most of the research has been carried out on children. (15) The CRA is more important in people who have inadequate socioeconomic status and further attention should be paid to this group of people.…”
Section: Discussionmentioning
confidence: 99%
“…Goldfeld et al showed that caries were higher in children with lower socioeconomic status. (14) Factors such as the socioeconomic status represent a few key indicators of the disease, such as the socioeconomic status, and risk factors such as microflora determines that the person is at a low, moderate and high risk of caries, although most of the research has been carried out on children. (15) The CRA is more important in people who have inadequate socioeconomic status and further attention should be paid to this group of people.…”
Section: Discussionmentioning
confidence: 99%
“…A secondary analysis of a nation‐wide longitudinal birth cohort study of Australian children also contributed evidence of impact of water fluoridation on socioeconomic inequalities in child oral health …”
Section: The National Guidelines On Fluoride Use 2019mentioning
confidence: 99%
“…A secondary analysis of a nation-wide longitudinal birth cohort study of Australian children also contributed evidence of impact of water fluoridation on socioeconomic inequalities in child oral health. 34 The 2019 Guidelines on water fluoridation Therefore, the Workshop supported the continuation of water fluoridation at current Australian levels and recommended:…”
Section: Effectiveness Of Water Fluoridationmentioning
confidence: 99%
“…A number of longitudinal studies used only self-reported oral health outcomes. 10 11 Furthermore, timing of and interaction between these exposures in early childhood are potentially important. We lack crucial longitudinal evidence to comprehensively evaluate the timing and interaction between risk and protective factors influencing caries experience through childhood.…”
Section: Introductionmentioning
confidence: 99%